Perbedaan Konsumsi Pangan dan Asupan Gizi pada Balita Stunting dan Normal di Lima Provinsi di Indonesia - Mariana Prijono; Nuri Andarwulan; Nurheni Sri Palupi (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2020)
Stunting is an important sign of chronic malnutrition that exists in early life with greater infection risk and with many long-term effects, including the need for physical work. Stunting is a problem for the Indonesian people to produce a generation that has global competitiveness. In general, this study aims to determine the effect of food consumption on the adequacy and balance of nutrition between stunted and normal children in 5 provinces in Indonesia. Specifically, this study aims to (1) lassify toddlers based on height according to age in the stunting and normal categories, (2) get a profile of stunting and normal toddler food consumption, (3) analyze data on nutrient intake and food contribution in the stunting group and normal, (4) analyze data on the adequacy and balance of nutrition from food intake in stunting and normal children under five in 5 provinces in Indonesia. This study used secondary data of food consumption data from SKMI 2014 and anthropometric data from Riskesdas 2013 of West Java, Central Java, East Java, West Nusa Tenggara and East Nusa Tenggara provinces. There were 2,039 samples from 5 provinces, 38.4% of them were stunting toddlers. Food consumption of toddlers with normal height was higher than stunting toddlers for eggs and egg products and lower for sugars. Intake of calcium and vitamin A in normal toddlers was significantly higher than stunting toddlers and lower for vitamin C. Both stunting and normal children groups showed deficiency, sufficiency and excess in nutrient intake. Imbalance nutrient intake for both stunting and normal children reached 100%.